Artificial Intelligence in Human Resources Management - Paing, Johan (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Artificial Intelligence (AI) began to emerge in the mid-20th century. However, there has been a lack of consistency in views regarding AI within the scope of Human Resource Management (HRM). Initially, AI and HRM were two separate streams of research. Currently, AI and HRM have been analyzed together to gather knowledge and identify common patterns of interaction between the two. The research method employed in this study is a systematic literature review of 65 scientific articles published in international journals, with primary sources from Scopus Elsevier, Web of Science (WOB), and Google Scholar. This paper outlines the analysis of how HRM influenced by AI and describe a concept of AI within HRM. Furthermore, many application of AI within HRM are also analyzed. Subsequently, the development of AI-based robotics technology and its impacts are discussed. Finally, a literature review framework for future research will be presented.